Occupational downgrading and bumping down : the combined effects of education and experience - Léné, Alexandre [Verfasser] (My University, 2011)
"Job competition between workers has important implications for 'downgrading' and 'bumping down'. To account for these phenomena, a matching model is considered in which highly educated and poorly educated workers compete for skilled jobs. An exogenous increase in the proportion of highly skilled workers increases the proportion of these workers in low-level jobs (downgrading). Another of the paper's findings is that changes in the composition of the workforce affect workers' opportunities to accumulate experience. An increase in the relative supply of highly educated workers reduces the opportunities for poorly educated workers to learn on the job. Both education and experience are required in order to access skilled jobs." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; G 1.2 Arbeitsmarkt; G 1.3.3.1 Qualifikationsverwertung; Bildungsniveau; Qualifikationsniveau; Überqualifikation; Hochqualifizierter; Geringqualifizierter; Wettbewerb; Arbeitsmarkt; Arbeitsmarktsegmentation; Arbeitsmarktchance; Facharbeiterberuf; Mittlere Qualifikation; Mathematisches Modell; Europäische Union; OECD-Staaten